Freudian Psychoanalytic Exploration of Will Freeman's Transformation into an Impromptu Parent in Nick Hornby's 'About a Boy' - Nurdin, Muhammad Pasha Nabih; Anam, Zuhrul (Universitas Muhammadiyah Barru, 2025)
Through the lens of Sigmund Freud's psychoanalytic theory—specifically, the id, ego, and superego this study examines the psychological development of Will Freeman, the main character in Nick Hornby's novel About a Boy. The purpose of the paper is to reveal how Will's unconscious impulses and internal conflicts influence his development from a selfish bachelor to a dedicated, unintended father figure to a youngster named Marcus. The study examines a few chosen narrative scenes, conversations, and character interactions that illustrate Will's evolving mental state using a qualitative descriptive methodology. The changes in Will's psychological state were charted using data gathered from closely examining texts and evaluated using Freudian frameworks. The results show that Will's metamorphosis is fueled by an ongoing dialogue between his innate needs, realistically based reason, and growing moral consciousness, which is reflected in the major incidents and character interactions. By showing how Freudian theory can shed light on character development in modern fiction, the study advances psychoanalytic literary theory. It also sheds light on the wider ramifications of applying psychoanalytic frameworks to the analysis of contemporary stories' themes of identity, masculinity, and emotional development.